The Function of Code Mixing and Code Switching Uttered by Cinta Laura at Curhat Bang Denny Sumargo Youtube Channel - Fetri Reni (Fakultas Sastra Universitas Ekasakti, 2022)
Code-mixing and code-switching can effectively deal with the complex communicative demands that arise when participants have varied levels of linguistic ability. This paper aimed to examine the functions of code-mixing and code switching uttered by Cinta Laura Kiehl in Bang Denny Sumargo Interview Show on August 18th 2021 entitled “Terjebak Toxic Relationship'' (In A Toxic Relationship). The design of this study used a qualitative descriptive method. Data were gathered from the interview in written data. An explanatory sample was used to analyze the collected data.Cinta Laura is a bilingual person who has the ability to use two languages with the same good manner. It means that there is not more dominant between one language to another.Furthermore, the most dominant function of code-mixing was incompetence and the most dominant function of code-switching was covering the ability to speak a specific language. Study results are expected to contribute to students and lecturers of English and researchers engaging in sociolinguistic research to explore further the purpose of using code-mixing and code-switching in conversation.